KOMPARATIV LITTERATURHISTORIE I DET UDVIDEDE FELT - STILLEHAVET SOM CASE - Andersen, Frits (K&K - Kultur og Klasse, 2014)
KOMPARATIV LITTERATURHISTORIE I DET UDVIDEDE FELT. STILLEHAVET SOM CASE | The article discusses status and perspectives for writing literary history based on an updated model for comparative literature. While the American re-launching of World Literature is not regarded to be a useful response to the global challenges facing literary historiography, it is proposed to re-evaluate the long history of comparatism in order to find models that match the current situation of literature in the expanded field. The article investigates narratives on expeditions in the Pacific Ocean from the 18th century. Here are outlined two models for comparison: One that leads toward cultural relativism and its problematic tendency to describe the compared societies as autonomous and closed, and another model, which can serve as a point of departure for grasping literature in both its historical and global conditions.